Clinicoradiological Correlation of Macropsia due to Acute Stroke: A Case Report and Review of the Literature - Mayra Johana Montalvo; Muhib Alam Khan (Case Reports in Neurological Medicine)
Dysmetropsia (macropsia, micropsia, teleopsia, or pelopsia) most commonly results from retinal pathologies, epileptic seizure, neoplastic lesions, viral infection, or psychoactive drugs. Vascular lesions are an uncommon cause of dysmetropsia. Vascular hemimicropsia, although rare, has been more frequently described in the literature, whereas hemimacropsia from acute ischemic injury is exceedingly rare. We describe a patient presenting in the emergency room (ER) with visual perception disturbances characterized by a distorted perception of the size of objects, compatible with left hemimacropsia. Magnetic resonance imaging (MRI) of the brain showed an acute occipitotemporal ischemic injury corresponding to the posterior cerebral artery (PCA) territory. The location of the lesion is consistent with previous case reports that suggest that hemimacropsia is associated with the occipitotemporal projection, which plays a decisive role in the visual identification of objects by interconnecting the striate, prestriate, and inferior temporal areas. The difference of our case as compared to previous case reports is that the lesion in our patient spared Brodmann area 17 (calcarine cortex) and therefore did not present symptoms of quadrantanopsia. Instead, the patient presented isolated hemimacropsia, therefore suggesting that the anatomical lesion causing hemimacropsia is located in the ventral portion of the occipitotemporal projection, more specifically Brodmann areas 18 (parastriate) and 19 (peristriate).